Josué em cena : processos discursivos e assunção da autoria na obra Dona Anja - Cesaro, Lisiane de (2013)
The aim of this study is to investigate the discursive process concerning to the process of subject creation in an I elemental to authorship, i.e the subject formation in author present in Dona Anja by Josué Guimarães. This research intents analyzing the author marks present in handwritten version text to the first book´s edition. The topic investigation occur based in French Discourse Analyses to make this study possible we put in circulation some notions formulated by AD with the purpose to carry out our investigative trajectory proposed in the topic. These are fundamental notions to our investigation: subject, authorship, author-function, ideology, ideological formation and discursive formation. Considering that the linguistic materiality reveals the subject-position assumed by the author we intend to verify how the author makes subjective in the narrative and in what degree the ideological formations operate composing the text and the signification. It is in the perspective of observation and confrontation in the two versions of the narrative Dona Anja that we make our discursive process analysis, as well as the choices/ changes made by the author. We look for what is behind the words, what is not said, in the dislocation of sense, in the subject evidences submitted by the ideology and affected by unconscious, present in literary text that integrate Josué Guimarães´work and, in this way we seek verifying in our comparisons evidences to confirm the theory indications. We also desire, in this work, demonstrate the existent relation among literature, linguistic and ideology put into practice discourse a place of analysis because is by the language that the authorship, the ideology interpellates the subject making him in a author-subject. By analyzing the linguistic marks present in the handwritten text version we obtain clues to observe language operating. Considering the corpus, we try to comprehend in what proportion to ideology interpellates the subject and makes him a an author-subject an how he makes subjective in the text.It turns, special look for the question about what are the marks let by the author the shows his legend in an specific discursive formation